Manufacturing of coarse and ultrafine-grained aluminum matrix composites reinforced with Al2O3 nanoparticles via friction stir processing. (August 2022) - Orłowska, Marta; Pixner, Florian; Hütter, Andreas; Enzinger, Norbert; Olejnik, Lech; Lewandowska, Małgorzata
Abstract: The objective of this work was to manufacture, using friction stir processing (FSP), nanocomposites consisting of coarse grained (CG) and ultrafine-grained (UFG) aluminum (Al) matrix reinforced by Al2 O3 nanoparticles. The main focus of the study was to investigate the possibility of preserving high mechanical properties in the stir zone (SZ) of an UFG material, which is thermally unstable. The investigation consisted in characterizing the microstructure and evaluating the mechanical properties of the materials. Two FSP passes were sufficient to obtain a proper distribution of reinforcement in the UFG Al matrix. Due to the FSP process, the average grain size increased from 1 μm for the base material to about 4 μm for the nanocomposite and 12 μm for the sample processed without the reinforcement. However, due to the presence of the nanoparticles, a drop in tensile strength for the nanocomposite was only from 164 MPa to 148 MPa. While in the case of sample processed without Al2 O3 this value was significantly lower and estimated 93 MPa. Moreover, the addition of nanoparticles caused an increase in elongation to break from 9 % to 23 %, which is caused by to the proper distribution of the particles in Al matrix.